The effects of angiotensin-converting enzyme gene polymorphism on the progression of immunoglobulin A nephropathy in Malaysian patients - Draman, Che Rosle; Kong , NCT; Gafor, AH; Rahman, AFA; Zainuddin , S; Mustaffa, WMW; Radzi, AM; Shamsul , AS (Singapore Medical Association, 2008)
Introduction: Angiotensin-converting enzyme (ACE) gene polymorphism, especially the deletion/deletion (DD) genotype, is associated with the disease progression of immunoglobulin A (IgA) nephropathy patients in various studies from both Asia Pacific and European populations. However, recent studies within the same populations were unable to reproduce the same results. Hence, we had studied the distribution of the DD genotype, the association between ACE gene polymorphism and the disease progression, and the factors (other than ACE gene polymorphism) which were involved in the disease progression of our local patients. Methods: This was a cross-sectional study of biopsy-proven IgA nephropathy patients attending the Nephrology Clinic, Hospital Universiti Kebangsaan Malaysia. Both biochemical and urine tests at the time of first presentation were compared to those at the time of the study, and the disease progression was analysed. The ACE gene polymorphism was identified via PCR-amplification technique, and patients were then categorised into the DD and the non-DD groups for detailed analysis. Histological severity of each renal biopsy was scored according to the predetermined criteria and medications used were recorded. The association between the gene polymorphism and disease progression was then determined. The patients who were stable or had renal function deterioration, were respectively regrouped into Groups 1 and 2, to identity those factors (other than ACE gene polymorphism), which were involved in the disease progression. Results: 60 patients with adequate renal histopathological examination were recruited. Their mean age was 40.9 +/− 12.3 years and the follow-up duration was 4 +/− 3 years (range 6 months–20 years). More than two-thirds of them were treated with ACE inhibitors or angiotensin receptor blockers and 8.3 percent received the combination treatment. The DD genotype was noted in 13.3 percent of study patients, insertion/insertion in 48.3 percent and insertion/deletion genotype in 38.3 percent. Although the estimated glomerular filtration rate (eGFR) of both groups were the same during their initial presentation, the DD patients had more severe disease compared to the non-DD patients at the time of the study. Their serum creatinine and eGFR was 178 (IQR 31.3) μmol/L and 42.1 +/− 31.1 ml/min/1.73 square metres, whereas the non-DD patients had serum creatinine and eGFR of 79 (IQR: 88.3) μmol/L and 76.6 +/− 42.1 ml/min/1.73 square metres, respectively (p-value is less than 0.01). The DD patients were also found to have more severe vascular damage in their renal biopsies compared to the non-DD patients. The annual rate of decline in eGFR was not significantly different between the two groups. It was −5.7 +/− 2.2 ml/min/1.73 square metres/year for the DD group and −4.8 +/− 2.0 ml/min/1.73 square metres/year for the non-DD group (p-value is equal to 0.5). They also had severe proteinuria with UPCI of 0.09 (IQR 0.2) g/mmol creatinine vs. 0.04 (IQR 0.10) g/mmol creatinine (p-value is less than 0.01). The study also confirmed that patients who had higher systolic blood pressure, greater proteinuria and longer follow-up duration had significant renal function deterioration compared to those who did not. Conclusion: The DD genotype, although found in a minority of the patients, might have adversely affected the disease progression of our IgA nephropathy patients. Higher systolic blood pressure, greater proteinuria and longer follow-up duration were the other prognostic factors in IgA nephropathy patients. However, appropriate treatment, especially prompt use of renin-angiotensin-aldosterone system blockade, should stabilise the disease regardless of their genotype